PENGARUH FRAKSI VOLUME PENGUAT 2, 2,5 DAN 3% SERAT BAMBU HAUR DAN FIBERGLASS TERHADAP KEKUATAN TARIK MATRIKS POLIESTER - Raliannoor Raliannoor; Dwi Rahmalina (INFO-TEKNIK, 2019)
Against the backdrop of the increasing need for quality composite materials and the development of increasingly advanced composite manufacturing technology in the machinery industry. The aim of this research is to develop composite materials with bamboo fiber reinforcement and glass fiber as an alternative to automotive raw materials to replace plastic. Preparation of composite specimens with each reinforcement with volume fractions of 2%, 2.5%, and 3% and specimens without reinforcement or 0% volume fraction as a comparison. The polymer material used is Yukalac 157-EX BQTN polyester as its matrix. With haur bamboo fiber and fiberglass as a reinforcement. Making specimens using the hand lay up method. Tests carried out are composite specimen tensile tests. Tensile testing was carried out using the ASTM D 638M-84 M-1 standard. Based on the test results, it was concluded that the effect of fiber volume fraction on the characteristics of composite samples for tensile tests. Composite strengthened by haur bamboo and fiberglass powder at 3% heavy volume fraction has the most ideal characteristics that have a tensile strength of 53.581 MPa, modulus of elasticity of 87.452 MPa and polymer composite material with a strength of haur bamboo and fiberglass powder with a length of 5 mm at 3% reinforcing volume fraction can be used as an alternative to automotive raw materials, namely replacing polyoxymethylene plastic materials for the front bumper.